EVALUASI KESESUAIAN LAHAN TANAMAN BUAH NAGA (Hylocereus undatus) DI DESA MAKU, KECAMATAN DOLO, KABUPATEN SIGI, PROVINSI SULAWESI TENGAH - Marwah, Marwah; Isrun, Isrun; Amelia, Rezi (AGROTEKBIS, 2018)
This research aim was toevaluate land suitability for dragon fruit plantation in Maku village, Dolo sub district, Sigi Regency, Central Sulawesi Province. Seven land units were evaluated for their suitability. Survey was conducted in seven land units for observation on soil drainage, slope, stones, and root depth. Undisturbed and disturbed soil sample were taken from each land unit for physical and chemical analyses in the Soil Laboratory of Agriculture Faculty Tadulako University. Of the seven land units, one land unit was classified as actual N1 (currently not suitable), another one land unit as S2 (moderately suitable) whereas the other five land units were categorized as actual S3(marginally suitable). The limiting factorsconsisted of texture, water, and soil pH. By correcting all the limiting factors existing in all land units, the actual classes of N1, S3 and S2 can be changed into the potential classes of S3, S2, and S1, respectively.